A Model for Technology Adoption, Financial Literacy, and Growth of Internet Banking in Centenary Bank Branches in Uganda - Kagoya , Sumaya M.; Yapkoreny, Esther (University of Dar es Salaam Library Journal, 2024)
This study examined the relationship between technology adoption, financial literacy, and the growth of Internet banking in Centenary Bank branches in Uganda and it specifically based on three objectives to examine the relationship between technology adoption and Internet banking, financial literacy and the growth of Internet banking, and to examine the combined effect of technology adoption and financial literacy on Internet-banking A cross-sectional research and quantitative design was adopted with a sample size of 108 employees from a population of 150 determined by Krejcie and Morgan's (1970) table. The data was tested for reliability and validity, analysed using SPSS v23 and results presented based on the study objectives. Findings revealed a significant and positive relationship between technology adoption and Internet banking given by (r=.380** and p<.01). Further findings indicated that there is a positive significant relationship between financial literacy and growth of Internet banking given by (r=.591** and p<.01). Overall technology adoption and financial literacy explain 34.5% of the variance in Internet-banking. In addition, financial literacy was found a stronger predictor (Beta = .539, sig. <.000) of Internet-banking compared to technology adoption (Beta = .101, sig. <.001). Therefore, recommendations are detailed in the main document for further guidance.